2021
DOI: 10.1039/d1gc02402g
|View full text |Cite
|
Sign up to set email alerts
|

Furan platform chemicals beyond fuels and plastics

Abstract: The article offers some perspective on the metamorphosis which already began to take place in substantial parts of the chemical industry – a switch from traditional resources such as crude...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 308 publications
0
47
0
Order By: Relevance
“…[11][12][13] During the past few decades, chemical conversions of cellulose have been widely reported and offered various value-added chemicals including monosaccharides, 14 polyols, 15 furans, 16 organic acids, 17 hydrocarbons, 18 esters, 19 among others, which have numerous applications in the chemical and energy industries. 20,21 All these advances have demonstrated the great potential of cellulose as a feedstock for renewable energies.…”
Section: Jin-yue Luomentioning
confidence: 99%
“…[11][12][13] During the past few decades, chemical conversions of cellulose have been widely reported and offered various value-added chemicals including monosaccharides, 14 polyols, 15 furans, 16 organic acids, 17 hydrocarbons, 18 esters, 19 among others, which have numerous applications in the chemical and energy industries. 20,21 All these advances have demonstrated the great potential of cellulose as a feedstock for renewable energies.…”
Section: Jin-yue Luomentioning
confidence: 99%
“…80 Furfural and HMF are bio-based renewable feedstocks, and their oxidation products are important for the implementation of future green chemical industry. 81,82 It was found that while in the presence of other pyridine-based pincer complexes furfural and HMF degraded to unidentifiable polymers, the acridine-based complexes selectively oxidized them with high yields (495%), while suppressing decomposition. Mechanistic experiments indicated that the employed aromatized complex is dearomatized in the initial step to generate complex 4, which subsequently catalyses the reaction.…”
Section: Deaminative Oxidation Of Amines To Acidsmentioning
confidence: 99%
“…[1][2][3] As a typical representative, 5-hydroxymethylfurfural (HMF) is gaining more and more concern and interest of researchers around the world, [4][5][6] and at the same time, its further upgradation is recognized as a very promising strategy to produce high-value derivatives. [7][8][9] In this context, converting HMF to 2,5-bis(hydroxymethyl)furan (BHMF) is highly conspicuous [10][11][12] because BHMF is an important furanyl diol with a symmetrical structure, endowing it with wide applications in the synthesis of various bio-based fuels, [13][14][15] polyethers, [16][17][18] polyesters [19][20][21][22] and polyurethanes. [23][24][25][26] However, it is noteworthy that HMF simultaneously contains reducible −CvO, −C−O and −Cv moieties, and when it is hydrogenated, many products can be synthesized.…”
Section: Introductionmentioning
confidence: 99%